(untitled) (Annals of Medical Research, 2022)
Aim: Smoking and Hookah is widespread in Western countries and in the United States. The goal of this study was to compare the genotoxic/mutagenic effects of cigarettes and hookahs in oral mucosa cells using the micronucleus biomarker to see if there was a difference between the two types of fumes. Materials and Methods: In the current study, 75 people were chosen at random from various parts of Duhok, Iraq. They were divided into three groups (25 participants for each group): a control group, a group of cigarette users only, and a group of narghile users only. The total number of micronuclei per 1,000 cells per subject was compared under light microscope. Results: According to the findings, the groups with the highest frequency of micronucleus were those who only used hookah (10.2±9), followed by cigarette users (8.3±4) and non-smoker participant (2.5 ±7). Hookah use was found to be more genotoxic than tobacco consumption. Conclusion: Cigarette and Hookah smoking had a significantly greater cytotoxic effect on buccal mucosa cells than nonsmokers. Increasing the duration of smoking could increase the frequency of micronucleus.